Three-dimensional computed craniofacial tomography (3D-CT): potential uses and limitations - Chan Hong Jin; Woods Michael; Stella Damien (Sciendo, 2023)
To determine the potential uses and limitations of 3D-CT craniofacial imaging in contemporary clinical practice.